Early Brazil : a documentary collection to 1700 - Schwartz, Stuart B. (New York : Cambridge University Press, 2010)
"Early Brazil presents a collection of original sources, many published for the first time in English and some never before published in any language, that illustrates the process of conquest, colonization, and settlement in Brazil. The volume emphasizes the actions and interactions of the indigenous peoples, Portuguese, and Africans in the formation of the first extensive plantation colony based on slavery in the Americas, and it also includes documents that reveal the political, social, religious, and economic life of the colony. Original documents on early Brazilian history are difficult to find in English, and this collection will serve the interests of undergraduate students, as well as graduate students, who seek to make comparisons or to understand the history of Portuguese expansion"--Provided by publisher.
Machine generated contents note: 1. The 'discovery' and first encounters with Brazil; 2. The donatarial system; 3. Royal government; 4. The French interlude; 5. Indians, Jesuits, and colonizers; 6. The world of the engenhos; 7. Government and society in Dutch Brazil; 8. Burdens of slavery and race: the war against Palmares; 9. Public and private power; 10. Religion and society; 11. Frontiers.
Includes bibliographical references and index.
Keywords: Brazil -- History -- To 1822 -- Sources